Do NCCHC Dental Standards Have Any Teeth?. (July 2016) - Douds, Anne S.; Ahlin, Eileen M.
Federal civil rights law establishes legal parameters for correctional dental care, but it does not provide specific standards for implementation. Thus, courts have developed guidelines on a case-by-case basis, often rendering the National Commission on Correctional Health Care (NCCHC) standards on dental care the de facto benchmark for institutions. This systematic review of all court cases that apply NCCHC standards for dentistry in prisons examines how courts use NCCHC standards and provides insights into whether those standards have any "teeth, " or power, in a legal sense. These findings consider the legal relevance of NCCHC standards and speak more broadly to the role of professional organizations in the legal and correctional communities.